(3NWI GdYed GdhWfjI ddbVGA Ydi CShC CTcGd Yed GdCWaGd aj dHfGf HMdhd GdYGe (B2016s - (3hRGQI GdYed s; (3efXeI GdYed GdOhdjI s; (3GddLfI GdhWfjI decGaMI Yed GdCWaGds ((3HjQhJs (3hRGQI GdYed GddHfGfjI (B/ (3efXeI GdYed GdOhdjI (B/ (3GddLfI GdhWfjI decGaMI Yed GdCWaGds, 2013)
(3jYQV gPG GdJbQjQ dNWI GdYed GdhWfjI ddbVGA Ydi CShC CTcGd Yed GdCWaGd aj dHfGf HfgGjI GdYGe(B2016 (3, eJUhQG Cf GdLghO GdeHPhdI SJDOj Edi hYj CcHQ JLGg eTcdI Yed GdCWaGd HTcd YGe hEdi GfNaGV aj YOO GdCWaGd GdYGedjf aj dHfGf(B. (3TGQc YOO ef GdeSDhdjf ef hRGQGJ heDSSGJ GdeLJeY GdeOfj aj EYOGO NWI GdYed GdhWfjI hGdeUGObI YdjgG, hbO SGgehG aj EZfGA GdefGbTGJ hEVGaI YfGUQ hGbYjI YdjgG(B. (3ceG Je CNP YOO dG HCS Hg ef hLgGJ fXQ GdCWaGd GdYGedjf hChdjGA CehQge, CKfGA EYOGO GdNWI(B. (3hGQJcRJ GdNWI Ydi KdGK QcGFR CSGSjI, GdQUO, GdJbjje, hJbOjQ GdCKQ(B. (3Cj LeY hJMdjd LejY GdeYdheGJ GdeJYdbI HJfajP GdNWI HTcd OGFe hefgLj, ef HYOgG Jbjje aGYdjI hUhGHjI GdJfajP hEUOGQ GdJhUjGJ GddGReI GdeJYdbI HGdJbhje MjK JbJVj GdMGLI, hef Ke bjGS GdfJGFL GdJj COJ Edi JZjjQ aYdj hEjLGHj aj MjGI GdCWaGd GdPjf GfJTdhG ef CShC CTcGd GdYed, Ch aj MjGI GdCWaGd GdYGedjf HTcd YGe(B. (3Je GdGJaGb aj GdfgGjI Ydi JCdja dLfI JbfjI, ef cd GdhRGQGJ GdeYfjI, dhVY eMUdI cd gPg GdedGMXGJ aj hQbI hGMOI(B. (3hJDcO NWI GdYed GdhWfjI CjVG Ydi GdJRGe dHfGf HGdgOa GdYGdej GdeJeKd HGdbVGA Ydi CShC CTcGd Yed GdCWaGd HMdhd YGe (B2016.s
(3GdfhY (B: (3JbQjQs
Keywords: Child Labor; Ministere du Travail; Ministry of labour; Travail des enfants; (3YeGdI GdGWaGd hCWaGd GdThGQYs; (3hRGQI GdYeds